Perioperative myocardial injury in patients with coronary artery disease during elective lower limb surgery - Yu. A. Kudaev; A. V. Vorobeva; N. L. Lokhovinina; I. T. Abesadze; M. Z. Alugishvili; I. V. Titenkov; M. A. Chernyavsky; A. V. Panov (Рациональная фармакотерапия в кардиологии, 2023)
Aim. To assess the prevalence of ischemic myocardial injury and the cardioprotective effect of nicorandil by assessing high-sensitivity cardiac troponin (hs-cTn) in patients with stable coronary artery disease (CAD) during elective lower limb surgery, as well as to identify predictors of adverse cardiac events.Material and methods. The study included 70 patients with stable coronary artery disease hospitalized for elective autogenous femoropopliteal bypass (FPB) surgery. After randomization, all patients were divided into two following groups: control group — 35 patients; main group — 35 patients, who, in addition to standard therapy, were prescribed nicorandil (Cordinic, PIQ-PHARMA) in a single dose of 20 mg 2 hours before surgery. In the postoperative period, the incidence of myocardial injury was assessed by hs-cTn increase. The obtained primary data were subjected to mathematical processing using the R-Studio software package (R language).Results. At baseline, patients in both groups were comparable in clinical characteristics, therapy, and duration of vascular surgery. In the main group of patients receiving nicorandil, a significant decrease in the incidence of perioperative myocardial injury was noted. In 5 patients of the control group, hs-cTn level 24 hours after surgery exceeded the threshold value, which indicated myocardial injury in the early postoperative period. In the nicorandil group, there was no hs-cTn increase (14% vs 0%, p=0,027). Regression analysis identified a predictor of perioperative myocardial injury — left ventricular ejection fraction (LVEF) <50%. LVEF <50% increases the risk of myocardial injury in the early postoperative period by 7,36 times (p=0,04) and 9,15 times (p=0,048) according to univariate and multivariate regression analysis, respectively.Conclusion. Perioperative myocardial injury is a common complication in patients with CAD undergoing lower extremity revascularization. The use of nicorandil (Cordinic, PIQ-PHARMA) before elective revascularization surgery helps reduce the incidence of ischemic myocardial injury in the early postoperative period and is not accompanied by adverse reactions, which rationales this approach to improve the clinical outcomes of lower extremity revascularization in patients with stable CAD. A predictor of myocardial injury, determined by hs-cTn, is a LVEF <50%.